2002
DOI: 10.1007/s00134-002-1574-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the practice of non-invasive ventilation in treating COPD patients over 8 years

Abstract: We conclude that, over time, experience with NIV may progressively allow more severely ill patients to be treated without changing the rate of success. The daily cost of NIV per patient can be reduced by treating less severely ill patients outside the RICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
0
6

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(92 citation statements)
references
References 29 publications
5
81
0
6
Order By: Relevance
“…This is in agreement with previously published data that showed that increasing experience with NIV may progressively allow more severely ill patients to be treated without changing the NIV success rate. 33 The crude mortality rates found in the 2 Italian RHDCU surveys are similar to those reported for COPD exacerbations managed with NIV (10 -25%). [34][35][36] However, those data were obtained from hospital discharge sheets, which lack information about important confounders such as disease severity, comorbidities, and interventions.…”
Section: Interventions Diseases and Outcomessupporting
confidence: 75%
“…This is in agreement with previously published data that showed that increasing experience with NIV may progressively allow more severely ill patients to be treated without changing the NIV success rate. 33 The crude mortality rates found in the 2 Italian RHDCU surveys are similar to those reported for COPD exacerbations managed with NIV (10 -25%). [34][35][36] However, those data were obtained from hospital discharge sheets, which lack information about important confounders such as disease severity, comorbidities, and interventions.…”
Section: Interventions Diseases and Outcomessupporting
confidence: 75%
“…Indeed, it is our policy to treat all patients with a COPD exacerbation with respiratory failure and a pH Ͼ 7.25 in the respiratory ward. 30 Only a small proportion of our patients were discharged to home from the RICU, in line with data reported by Bigatello et al, 19 who reported that only 2% of their patients were discharged to home.…”
Section: Discussionsupporting
confidence: 91%
“…However, the reported data do not necessarily imply that there is a lack of awareness about NIV failure risk; on the contrary, they could 18,19 NIV use in general wards is an area of research that has been largely neglected compared with studies performed in ICUs. The fact that almost all published studies on NIV were performed in ICUs could be misleading, as the results might not accurately represent where NIV is currently used in the real world.…”
Section: What This Paper Contributes To Our Knowledgementioning
confidence: 88%